Cytogenetic abnormalities in systemic mastocytosis: WHO subcategory‐specific incidence and prognostic impact among 348 informative cases. Issue 12 (26th September 2018) - Shah, Sahrish; Pardanani, Animesh; Elala, Yoseph C.; Lasho, Terra L.; Patnaik, Mrinal M.; Reichard, Kaaren K.; Hanson, Curtis A.; Ketterling, Rhett P.; Tefferi, Ayalew
Abstract: The World Health Organization (WHO) system lists five morphological categories of systemic mastocytosis (SM): indolent (ISM), smoldering, SM with an associated hematological neoplasm (SM‐AHN), aggressive (ASM) and mast cell leukemia (MCL). Recent studies have highlighted the prognostic importance of mutations in SM, including ASXL1, RUNX1, and SRSF2. In contrast, information on incidence of cytogenetic abnormalities in SM and their prognostic relevance, especially in the context of mutations, is limited. In the current study, we retrospectively reviewed the cytogenetic findings in 348 consecutive cases of SM (median age 59 years; 53% males); 41% constituted ISM, 45% SM‐AHN, 14% ASM and two cases of MCL. Karyotype was abnormal in 53 (15%) cases with incidences of 6% for ISM, 26% for SM‐AHN and 8% for ASM ( P  < .001); among SM‐AHN cases, abnormal karyotype incidences were 0% for SM‐AHN‐lymphoid and 28% for SM‐AHN‐myeloid ( P  < .001). Clinical correlative studies disclosed significant associations between abnormal karyotype and male sex ( P  = .002), age > 60 years ( P  = .04), thrombocytopenia ( P  < .001) and anemia ( P  < .001), but not with the presence of adverse mutations ( P  = .19). In univariate analysis, abnormal karyotype was associated with inferior survival (HR 3.0, 95% CI 2.0‐4.3), specifically confirmed for ASM (HR 4.9, 95% CI 1.1‐16.1) and SM‐AHN (HR 1.8, 95% CI 1.2‐2.7). Sample size adequacy allowed additional multivariable analysis in SM‐AHN‐myeloid, which disclosed independent prognostic contribution from adverse mutations ( P  = .003), anemia ( P  = .003) and thrombocytopenia ( P  = .001), but not from abnormal karyotype ( P  = .31). Our observations suggest that mutations are prognostically more relevant than karyotype in SM.